PENGARUH CAMPURAN TEPUNG KEPALA UDANG PADA PAKAN KOMERSIL TERHADAP PERTUMBUHAN IKAN NILA (Oreochromis niloticus) - Tiara Dwi Sandri; Eri Yusni (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2018)
Tilapia (Oreochromis niloticus) is a freshwater fish that has high economic value and widely cultivated, but the cultivators often get problem in feed prices because the high cost of raw materials such as fish feedwhich is still imported. To overcome this problem, we look for alternatives to local raw materials that can replace fish feed such as shrimp head waste flour. This study aims to determine the effect of shrimp head flour on commercial feed on the growth rate of tilapia. This study used a complete random planning which is designed with 3 treatments and 3 replication, P1 (75% commercial feed + 25% shrimp head flour), P2 (50% commercial feed + 50% shrimp head flour), P3 (25% commercial feed + head flour 75% shrimp). The data obtained were analyzed by variance and continued with Duncan's test. The parameters that observed were heavy and long growth, and the Feed Convertion Ratio (FCR). All parameters were showed that the use of shrimp head flour in artificial feed gave a very significant effect on the growth rate of tilapia with high growth values, while the FCR value was low. The high content of shrimp head flour in feed causes increased growth of tilapia. The results showed that the highest increase in length and weight with feed in P3 was found significant effect with value of length of 5.7 cm and weight of 21.2 g and the highest survival rate at P3 treatment of 80% and feed conversion ratio (FCR) of 0.8%.Keywords: Shrimp Head Flour, Growth Rate